ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, DESAIN PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN COLD STORAGE (Studi pada konsumen PT. USAHA MUDA PUTRA JAYA) - Guntoro, Hermawan; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2017)
This research reliable by the decreasing sales of cold storage at PT. USAHA MUDA PUTRA JAYA for several months. Then some factors that influence the purchase decision are need based on that public. This research is intended to know the perception effect of price, service quality, product design, and brand image on purchase decisions of cold storage at PT. USAHA MUDA PUTRA JAYA and determine what variable which has the greatest influence on purchase decisions of cold storage at PT. USAHA MUDA PUTRA JAYA.The research data were collected from 100 consumers of PT. USAHA MUDA PUTRA JAYA. The used sampling technique choose in this reseach is purposive sample technique. Then the analysis in this research is multiple linear regression analysis. The validity, reliability and classical assumption had been usually tested before. After multiple linear regression analysis has been done, hypothesis and the coefficient of determination test was done. The results of the research is the following regression equation: Y = 0.162 X1 + 0.155 X2 + 0.512 X3+ 0.172 X4.The results of multiple linear regression analysis showed variables of price, service quality, product design, and brand image perception have positive influence on purchase decisions. The variable which has the bigest impact is the products design, followed by brand image and price perception, while smallest effect is on the service quality. The analysis result by using Uji T showed that perceptions of price, service quality, product design and brand image individually has significant influence on purchasing decisions. This equation model has F value of 369.929 with a significance level of 0.000. The results of analysis by using the coefficient of determination indicated that about 93.7% of the purchase decision can be explained by the perception of price, service quality, product design and brand image, while 6.3% is explained by other variables that are not used in this research.